Оptimization of the chrome plating bath operation during the restoration of vehicle parts - A. N. Kotomchin (Вестник СибАДИ, 2021)
Introduction. In the process of chrome plating of car parts, there is a change in the composition of the chrome plating bath, which affects the stability of the ongoing processes – the performance and quality of the chrome coating. Therefore, it is necessary to constantly monitor the chrome plating bath for the presence of foreign elements that can be formed during the operation of the bath during the reaction of the solution with the anode or cathode.Materials and methods. During the research, the necessary equipment was used, which made it possible to determine with sufficient accuracy the content of trivalent chromium and its effect on the electrolysis process – the performance and quality of chrome coatings. A well-known technique was used to determine the quality and performance.Results. When conducting studies of the obtained cold self-regulating chromium plating electrolyte, it was found that trivalent chromium has a significant effect on the stability of the chromium plating bath. The content of which can vary within 2...25 g/l during operation. As a result, it was found that the optimal amount of trivalent chromium is its content in the chromium plating bath from 2 to 15 g/l. With a lower or higher content, the electrolysis performance and the quality of the chrome coating decrease. It was also found that in order to maintain the optimal amount of trivalent chromium and increase the time for stable operation of the chromium bath, it is necessary to observe the ratio of the area of the anode and cathode (the coated surface of the part), the value of which is within 3...4.Discussion and conclusion. As a result of the conducted research, it will make it possible, under certain conditions, to carry out the process of chromium deposition from a cold self-regulating electrolyte, which will allow for stable chromium deposition at high productivity and the necessary quality of the coatings obtained. The main condition is to control and maintain the amount of trivalent chromium in the chromium plating electrolyte in the bath.